Zur Negation im Gegenwartsdeutschen und im Modernen Hocharabisch Eine linguistisch-kontrastive Untersuchung - Qaddioui, Ouafaa (Heidelberg University Publishing (heiUP), 2020)
The present study is a contrastive and empirical investigation of the negative markers nicht in contemporary German (CG) and laysa, lam, lan, lammā, lāta, lā and mā in Modern Standard Arabic (MSA). Four aspects are analyzed from a comparative point of view: (i) the morphological fusion of the negative markers with indefinites in CG and with clitic particles/suffixes in MSA, which creates a paradigm of negative markers similar to an auxiliary verb paradigm, (ii) the position of those markers in sentence structures, (iii) the interaction between negative markers and verbal or nominal categories, and (iv) the interactions between negation and information structure. Two novels were chosen as the main sources of sample data: "Sommerstück" (1989) ("Piece of Summer") by Christa Wolf for CG and "Bayna al-Qasrayn" (1956) ("Palace Walk") by Naǧib Maḥfūẓ for MSA. The goal of the study is to describe and compare the grammatical organization of negation in both languages.